Armenians in the Byzantine Empire - Bromige, Toby. (London ; New York)
xi, 188 sayfa, [3] sayfa harita
Keywords: “Armenians in the Byzantine Empire is a new study exploring the relationship between the Armenians and Byzantines from the ninth through eleventh centuries. Utilising primary sources from multiple traditions, the evidence is clear that until the eleventh century Armenian migrants were able to fully assimilate into the Empire, in time recognized fully as Romaioi (Byzantine Romans). From the turn of the eleventh century however, migrating groups of Armenians seem to have resisted the previously successful process of assimilation, holding onto their ancestral and religious identity, and viewing the Byzantines with suspicion. This stagnation and ultimate failure to assimilate Armenian migrants into Byzantium has never been thoroughly investigated, despite its dire consequences in the late eleventh century when the Empire faced its most severe crisis since the rise of Islam, the arrival and settlement of the Turkic peoples in Anatolia.” --